Adolescent Self Reported Reproductive Morbidity and Health Care Seeking Behaviour - Rahman, M. Mizanur; Kabir, M.; Shahidullah, M. (Journal of Ayub Medical College Abbottabad, 2004)
Background: Addressing reproductive health issues of women is now on the global social agenda in the new millennium. Maternal mortality has long been the only indicator of women’s health even though reproductive morbidity occurs far more frequently and seriously affects women’s lives. In this paper, an attempt was made to assess the magnitude of self reported gynaecological morbidity unrelated to childbearing among the adolescents irrespective of their marital status. The paper also explored the determinants of health care seeking behaviour of the adolescents for their reproductive ailments. Methods: Both quantitative and qualitative data were collected for this study. Cross sectional study was conducted both in rural and urban areas using a multistage cluster sampling technique. A nationally representative data on 2883 adolescents irrespective of their marital status were analysed. Results: Analysis revealed that a large proportion of the adolescents (64.5%) reportedly has been suffering from gynaecological morbidity. The most frequent form of morbidity was menstrual disorders (63.9%) followed by lower abdominal pain (58.6%), burning sensation during urination(46.1%), genital itching (15.5%), vaginal discharge (3.4%) etc. Multivariate logistic regression analysis revealed that older adolescents aged 15-19 years, family income, type of family, type of residence and hygienic practice during menstruation appeared to be influencing factors for adolescents reproductive morbidity. The results also revealed that about one fifth (18.0%) sought health care for their gynaecological ailments indicating that adolescents were unaware about their reproductive morbidity (p<0.05). For assessing the factors influencing their health care seeking for reproductive morbidity, multivariate logistic regression analysis found significant positive association with adolescents aged 15-19 years, having autonomy in treatment, working status, adolescents of joint or extended family (p<0.05). Discussion: Adolescent reproductive health in Bangladesh indicates high incidence of maternal morbidity. The incidence of these health problems varied by socio-economic and demographic characteristics of the adolescents. Recommendations to address these problems include encouragement of female education, introduction of family life education in school curricula, creating community awareness for seeking health care and empowerment of women in household decision making process. Key Words: Adolescents, reproductive morbidity, care seeking behaviour, Bangladesh.